2021
DOI: 10.1063/5.0048900
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an ultrafast internal conversion pathway of pyrazine by time-resolved vacuum ultraviolet photoelectron spectrum simulations

Abstract: The internal conversion from the optically bright S2 ( 1 B2u, ππ*) state to the dark S1 ( 1 B3u, nπ*) state in pyrazine is a standard benchmark for experimental and theoretical studies on ultrafast radiationless decay. Since 2008 a few theoretical groups have suggested significant contributions of other dark states S3 ( 1 Au, nπ*) and S4 ( 1 B2g, nπ*) to the decay of S2. We have previously reported the results of nuclear wave packet simulations [Phys. Chem. Chem. Phys. 17, 2012] and photoelectron spectrum ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Experimentally, the photodynamics of pyrazine was studied by Suzuki and co-workers with femtosecond time-resolved photoelectron spectroscopy (TRPES) in the UV and very recently by Leone and co-workers with femtosecond X-ray absorption spectroscopy . The transient population of the dark A u state in the photophysics of pyrazine has become a controversially discussed topic in the recent literature. , While Suzuki and co-workers could not find evidence for the intermediate population of the A u state, Leone and co-workers reported detection of population in the A u state with a time delay of 200 fs . A recent computational simulation of the TRPES of pyrazine confirmed that the A u population indeed cannot be clearly distinguished from the B 3u population in TRPES .…”
mentioning
confidence: 99%
“…Experimentally, the photodynamics of pyrazine was studied by Suzuki and co-workers with femtosecond time-resolved photoelectron spectroscopy (TRPES) in the UV and very recently by Leone and co-workers with femtosecond X-ray absorption spectroscopy . The transient population of the dark A u state in the photophysics of pyrazine has become a controversially discussed topic in the recent literature. , While Suzuki and co-workers could not find evidence for the intermediate population of the A u state, Leone and co-workers reported detection of population in the A u state with a time delay of 200 fs . A recent computational simulation of the TRPES of pyrazine confirmed that the A u population indeed cannot be clearly distinguished from the B 3u population in TRPES .…”
mentioning
confidence: 99%
“…19,20 In particular, in their very recent study, Kanno et and Q 10a modes and found that this two-state model reproduces well the main features of the experimental timeresolved spectrum. 20 As Sala et al found that several modes of B 2g and B 3g symmetry need to be included in the three-state model to couple the 1 A u (nπ*), 1 B 2u (ππ*), and 1 B 3u (nπ*) states, 8 the minimum model of Kanno et al may have resulted in an incomplete description of the photophysics of pyrazine. The three-state ( 1 B 2u (ππ*), 1 B 3u (nπ*), 1 A u (nπ*)) nine-mode model of Sala et al 8 has been used to simulate time-and frequency-resolved fluorescence, transient absorption, and electronic two-dimensional (2D) signals of pyrazine.…”
Section: Introductionmentioning
confidence: 67%
“…Note, however, that we have not employed any scaling of the spectra in the energy domain. In contrast to the work of ref , in which plane-wave continuum orbitals were used, the static-exchange continuum orbitals used in the present work take the long-range Coulomb potential of the molecular cation into account. As a consequence, the photoionization cross section attains a finite value at the threshold, in contrast to the plane-wave cross section. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work we apply the SVD-based surprisal analysis 31 to identify the set of dominant observables that drive the S2-S1 non-radiative transitions in pyrazine. Internal conversion in pyrazine is extensively studied by various theoretical [42][43][44][45][46][47][48][49][50][51][52][53] and experimental methods. [54][55][56][57][58][59][60][61] Similar to other heteroaromatic organic chromophores, 13 strong non-adiabatic…”
mentioning
confidence: 99%